2014
DOI: 10.1212/wnl.0000000000001044
|View full text |Cite
|
Sign up to set email alerts
|

Changing outcome in inflammatory neuropathies

Abstract: The I-RODS more often captures clinically meaningful changes over time, with a greater magnitude of change, compared with the INCAT-ONLS disability scale in patients with GBS and CIDP. The I-RODS offers promise for being a more sensitive measure and its use is therefore suggested in future trials involving patients with GBS and CIDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(120 citation statements)
references
References 40 publications
2
114
1
3
Order By: Relevance
“…54 The utility of home evaluation of I-RODS has been previously discussed. 16 A small study found strong correlations between clinic and home evaluations of I-RODS and INCAT scores in leg function, although INCAT scores for arm function showed significant differences, with home evaluations typically scoring 1 point less. 55 In some clinical practices, frequent patient-reported grip strength collection at home with electronic communication to the physician is utilized to complement outcomes collected during routine clinical visits.…”
Section: Practical Application Of Outcome Measuresmentioning
confidence: 98%
See 2 more Smart Citations
“…54 The utility of home evaluation of I-RODS has been previously discussed. 16 A small study found strong correlations between clinic and home evaluations of I-RODS and INCAT scores in leg function, although INCAT scores for arm function showed significant differences, with home evaluations typically scoring 1 point less. 55 In some clinical practices, frequent patient-reported grip strength collection at home with electronic communication to the physician is utilized to complement outcomes collected during routine clinical visits.…”
Section: Practical Application Of Outcome Measuresmentioning
confidence: 98%
“…16 The I-RODS offers a more sensitive outcome measure than INCAT-ODDS or OLNS, and it has been proposed as the primary measure of disability in future clinical trials involving patients with GBS and CIDP. 17 Feasibility is both an advantage and potential limitation of the I-RODS.…”
Section: The Rasch-built Overall Disability Scalementioning
confidence: 99%
See 1 more Smart Citation
“…It pointed out a better evaluation of data analysis with the Rasch method, which enables a transformation of ordinal data into interval metric data, increasing the level of precision in the assessment. The Inflammatory Rasch-built Overall Disability scale offers the promise of being a more sensitive measure and is highly recommended in future trials involving patients with GBS and CIDP [101].…”
Section: Improvement In Assessment Of Dysimmune Neuropathies For Clinmentioning
confidence: 99%
“…First, the concept of MCID was applied to two outcome measures that are based on ordinal scales and are considered non-linear (INCAT and MRC) (Vanhoutte et al, 2013;Draak et al, 2014); therefore, the calculated MCID cut-off values may vary across the range of values for these scales (Merkies et al, 2010;Vanhoutte et al, 2013). Such variations in MCID have been demonstrated in several articles based on the varying measurement imprecisions (standard errors) (Heesch et al, 2006;Hobart and Cano, 2009;Vanhoutte et al, 2013).…”
mentioning
confidence: 99%